Evaluation of alternative disinfectants to formaldehyde for treating broiler eggs in a commercial hatchery - Wandrag, D.B.R. (University of Pretoria, 2023)
Dissertation (MMedVet (Veterinary Medicine))--University of Pretoria, 2022.